High Serum Elafin Prediction of Poor Prognosis of Locoregional Esophageal Squamous Cell Carcinoma - Wu, I-Chen (Cancers (Basel), 2021)
SIMPLE SUMMARY: Conventional serum markers such as carcinoembryonic antigen (CEA), squamous cell carcinoma antigen (SCC), and tissue polypeptide antigen (TPA) have a low sensitivity in predicting the prognosis of locoregional esophageal squamous cell carcinoma cell (ESCC). In our clinical study, we found high serum elafin to be an independent outcome predictor for stage I-IIIA ESCC, considering T, N, overall stage, and treatment. In vitro experiments showed that adding recombinant elafin drove ESCC cell proliferation, migration and invasion, while shRNA attenuated elafin levels, abrogating those effects. Our results suggested serum elafin might be a noninvasive biomarker to predict the outcome of locoregional ESCC and could potentially be used as a therapeutic target. ABSTRACT: Esophageal squamous cell carcinoma (ESCC) is a highly aggressive tumor known to have locally advanced and metastatic features which cause a dismal prognosis. We sought to determine whether elafin, a non-invasive and secretory small-molecule marker, could be used to predict prognosis in locoregional ESCC patients in human and in vitro studies. In our human study, 119 subjects were identified as having incident and pathologically-proved ESCC with stage I-IIIA tumors from southern Taiwan between 2000 and 2016. We measured their serum elafin levels at baseline and followed them until the date of cancer death or until January 2020, the end of this study. Those with high serum elafin levels were found to have a 1.99-fold risk (95% confidence interval: 1.17–3.38) shorter survival than those who did not. In our in vitro experiments, elevated elafin levels were found to drive ESCC cell proliferation, migration and invasion, while attenuation of elafin level by shRNA abrogated those effects. We concluded that elafin promotes ESCC motility and invasion and leads to a worse clinical prognosis in ESCC patients without distant metastasis.